(untitled) (Semiárida, 2020)
The objective was to evaluate changes in the botanical composition of a natural pasture of the Central Depression of Rio Grande do Sul due to different sources of phosphorus applied. Treatments consisted of a historic of application of 470 kg.ha-1.P2O5 in the sources single and triple super phosphate, Gafsa rock phosphate and introduction of cool season species and control. Except the control in all treatments were introduced ryegrass and clover. It was used BOTANAL method to assess flora composition. Multivariate analyzes were done ordering, by the method of principal coordinates, and randomization test, taking the Euclidean distance as a similarity measure using the software MULTIV. We identified 51 species on natural pasture. The botanical composition of the pasture was not altered by phosphorus sources when it was analyzed for all species (P= 0.262) but when it was assessed by species that contribute for more than 1% in forage mass (P= 0.066). The application of different sources of phosphorus changes the ranking order of species with higher herbage mass contribution in botanical composition of natural pasture.